2019
DOI: 10.3390/molecules24112120
|View full text |Cite
|
Sign up to set email alerts
|

The Methylene-Cycloalkylacetate (MCA) Scaffold in Terpenyl Compounds with Potential Pharmacological Activities

Abstract: Recently, the methylene-cycloakylacetate (MCA) scaffold has been reported as a potential pharmacophore for neurite outgrowth activity. In this work, natural diterpenes that embed MCA fragments are reviewed, as they are major components of Halimium viscosum: ent-halimic acid, the prototype for these bioactive compounds. Herein, structures, sources, and activities for the natural diterpenes, as well as their synthetic derivatives of interest, are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…In a recent study, we reported the synthesis of an unique family of methylene-cycloalkylacetate (MCAs)-based small molecule, (often observed as scaffold of various compounds and drugs of natural origin) neurotropic drug (inducing neurite/axonal outgrowth) and indicated that the alkene element, integrated within the cycloalkylacetate core, was obligatory for the neurotropic activity. , Additional studies have led to a wide variety of potential pharmaceutical candidates that share the methylene-cycloalkylacetate (MCA) scaffolds . Present study further characterizes the neurotropic activities of these compounds, specifically a candidate labeled HU-MCA-13, and analyzes its safety properties using blood biochemistry and cell counting, acute toxicity evaluation in mice and different in vitro “off-target” pharmacological evaluations.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In a recent study, we reported the synthesis of an unique family of methylene-cycloalkylacetate (MCAs)-based small molecule, (often observed as scaffold of various compounds and drugs of natural origin) neurotropic drug (inducing neurite/axonal outgrowth) and indicated that the alkene element, integrated within the cycloalkylacetate core, was obligatory for the neurotropic activity. , Additional studies have led to a wide variety of potential pharmaceutical candidates that share the methylene-cycloalkylacetate (MCA) scaffolds . Present study further characterizes the neurotropic activities of these compounds, specifically a candidate labeled HU-MCA-13, and analyzes its safety properties using blood biochemistry and cell counting, acute toxicity evaluation in mice and different in vitro “off-target” pharmacological evaluations.…”
Section: Introductionmentioning
confidence: 70%
“… 21 , 22 Additional studies have led to a wide variety of potential pharmaceutical candidates that share the methylene-cycloalkylacetate (MCA) scaffolds. 23 Present study further characterizes the neurotropic activities of these compounds, specifically a candidate labeled HU-MCA-13, 21 and analyzes its safety properties using blood biochemistry and cell counting, acute toxicity evaluation in mice and different in vitro “off-target” pharmacological evaluations. This MCA derivative deserves further preclinical mechanistic pharmacological characterizations and therapeutic efficacy in in vivo animal models of polyneuropathies toward development of a clinically relevant neurotropic drug.…”
Section: Introductionmentioning
confidence: 99%